POTENTIAL STUDY OF INDONESIA COAL FOR ADSORBED NATURAL GAS - Ika Monika (Puslitbang tekMIRA, 2016)
Low rank coal was used as a precursor for the preparation of adsorbed natural gas by chemical activation with KOH-NaOH mixtures. Chemical activation process is commonly used and involves two major steps, which are heating process and chemical treatment process. The experiments were used in the various of temperatures, contact times, and rasio of sample and chemical compound. The result of process was obtained of the iodine number around of 1004 mg/g and 1198 mg/g . Based on the other study, the iodine number at 1004 mg/g and 1198 mg/g have surface area between 1000 mg/g up to 1200 mg/g. These surface area provide a methane capacity between 75 mg/g up to 80 mg/g.